IoT-Based Automated Oxygen Pumping System for Acute Asthma Patients - A, Vidya V; T, Shynu; S, Shalima N; Rajest, Dr. S. Suman (European Journal of Life Safety and Stability (2660-9630), 2022)
This project presents an automatic oxygen pumping system for acute asthma patients. This system continuously monitors the patient’s breathing rate and starts pumping oxygen to support the patient’s breathing as soon as it identifies an abnormality. Meanwhile, it monitors the breath rate. If it finds the average rate is not achieved even after pumping, the controller sounds an alarm indicating the patient’s condition to the bystander. To monitor the patient’s breathing, a breath rate sensor is used. The controller adjusts a solenoid valve accordingly to pump oxygen when necessary. Also, we added a temperature sensor for measuring the body temperature, a heartbeat sensor for measuring the patient’s heart rate, and an IoT to send information to the consultant doctor’s PC or hospital.